2022
DOI: 10.1108/gkmc-10-2021-0171
|View full text |Cite
|
Sign up to set email alerts
|

Investigating antecedents of mobile payment systems’ decision-making: a mediated model

Abstract: Purpose The increase in mobile telephone penetration has offered new opportunities for technology to improve payment operations all over the world. Little research has examined the issues related to the decision-making (DM) of mobile payment systems usage in the Jordanian context. The purpose of this study is to examine the factors that may have an influence on the adoption of mobile payment systems. This study has empirically tested the expanded unified theory of acceptance and use of technology (UTAUT2) toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 65 publications
3
35
0
Order By: Relevance
“…The AVE ranged from 0.747 to 0.940 for all constructs. These estimates were way beyond the recommended lower limit of 0.50 (Sekaran and Bougie, 2016). Hence, the convergent validity in all three tests related to the scales was supported.…”
Section: Discussionmentioning
confidence: 77%
“…The AVE ranged from 0.747 to 0.940 for all constructs. These estimates were way beyond the recommended lower limit of 0.50 (Sekaran and Bougie, 2016). Hence, the convergent validity in all three tests related to the scales was supported.…”
Section: Discussionmentioning
confidence: 77%
“…Supporting facilities could include training, technical support, materials accessible to enhance users' skills and system accessibility. Previous studies also revealed the effects of the four constructs: PE, EE, SI and FC on the user's BI (Al-Okaily et al, 2022b;Tan, 2013;Wang et al, 2020). Drawing on the above discussion, the following hypotheses are inferred: H4.…”
Section: Theoretical Background and Research Modelmentioning
confidence: 79%
“…The empirical validation of the proposed model and hypotheses was done with SmartPLS 4 software analysis. This software has ability for analyzing complex models and it works well with small size data points as well as it commonly applied in IS research such as this one (Al-Okaily et al , 2022c, d, e, f). A SmartPLS algorithm, predictive and bootstrapping technique were run to determine loadings, path coefficients, determination coefficient, predictive relevance and significant levels.…”
Section: Discussionmentioning
confidence: 99%